Nasolabial appearance of bilateral cleft lip repair at five years of age. Comparing techniques of modified advancement-rotation (Delaire) with Manchester repair: a retrospective cohort study. Issue 10 (December 2021) - Thomson, R.M.; Jovic, T.; Drake, D.; O'Neill, T.
Abstract: The techniques used to repair bilateral cleft lip have evolved over time, yet little data exist to compare outcomes using the various techniques. The aim of this study was to retrospectively evaluate and compare the aesthetic outcomes of two types of complete bilateral cleft repair: advancement rotation and a historic cohort repaired with the Manchester technique. A total of 32 consecutive patients who had complete repair of bilateral cleft lips were identified retrospectively from our centre using inpatient records. The first 16 (born between 1994 and 2005) underwent the Manchester repair, the second 16 (born between 2006 and 2010) a Delaire modified advancement rotation technique. Standardised photographs were taken at five years post repair and cropped to isolate the nasolabial component. Appearance outcomes were assessed by 20 members of the cleft and plastic surgery team, who were each asked to rate all 32 images using the Asher-McDade five-point scale. A chi squared test was used to determine whether there was a statistically significant difference in cleft scores between the two approaches. There was a mean (SD) of 2.8 (1.02) in the advancement rotation group and a mean (SD) of 3.1 (1.07) in the Manchester group. There was a statistically significant difference in the distribution of scores in the advancement rotation group compared with the Manchester group, with lower scores (better results) in the advancement rotation group (p=0.003). This study demonstrates that the advancement rotation technique for the repair of bilateral cleft lip defects resulted in a superior nasolabial appearance when directly compared with the Manchester repair at 5 years of age.